Cerebral hemodynamic response to upright position in acute ischemic stroke - Carvalho, Lilian B.; Kaffenberger, Tina; Chambers, Brian; Borschmann, Karen; Levi, Christopher; Churilov, Leonid; Thijs, Vincent; Bernhardt, Julie (Frontiers in Neurology, 2024)
Introduction Concerns exist that a potential mechanism for harm of upright activity (sitting, standing, walking) early after an acute ischaemic stroke could be reduction of cerebral perfusion in this critical phase. We aimed to estimate the effects of upright positions (sitting, standing) on cerebral hemodynamics <48h and later 3-7 days post-stroke, in stroke with and without occlusive disease, and in controls. Methods We investigated MCAv using transcranial Doppler in 0° head position, then 30°, 70°, 90° sitting, and 90° standing, at <48h post-stroke and later at 3-7days post-stroke. Mixed effect linear regression modelling was used to estimate differences in MCAv between 0° other positions and to compare changes in MCAv across groups. Results Forty-two stroke participants (anterior and posterior circulation) (13 with occlusive disease, 29 without) and 22 controls were recruited. Affected hemisphere MCAv decreased in stroke with occlusive disease (<48h post-stroke): from 0° to 90° sitting (-9.9cm/s, 95%CI[-16.4,-3.4]) and from 0° to 90° standing (-7.1cm/s, 95%CI[-14.3,-0.01]). Affected hemisphere MCAv also decreased in stroke without occlusive disease from 0° to 90° sitting (-3.3cm/s, 95%CI[-5.6,-1.1]) and from 0° to 90° standing (-3.6cm/s, 95%CI[-5.9,-1.3]) (p-value interaction stroke with vs without occlusive disease=0.07). Decrease in MCAv at upright was also observed in controls from 0° to 90° sitting (-3.8cm/s, 95%CI[-6.0,-1.63]) and from 0° to 90° standing (-3cm/s, 95%CI[-5.2,-0.81]) (p-value interaction stroke vs controls=0.85). Subgroup analysis of anterior circulation stroke showed similar patterns of change in MCAv in the affected hemisphere, with significant interaction between those with occlusive disease (n=11) versus those without (n=26) (p=0.02). Changes in MCAv from 0° to upright at <48h post-stroke were similar to 3-7 days. No association between changes in MCAv <48h and 30-day modified Rankin Scale was found. Discussion Moving to more upright positions <2 days post-stroke does reduce MCAv on the affected hemisphere, but these changes were not significantly different for stroke participants (anterior and posterior circulation) with and without occlusive disease, neither for controls. Decrease in MCAv in anterior circulation stroke with occlusive disease was significantly different to without occlusive disease. However, the sample size was small, and more research is warranted to confirm these findings.